Digital play: a new classification. Issue 3 (2nd July 2016) - Marsh, Jackie; Plowman, Lydia; Yamada-Rice, Dylan; Bishop, Julia; Scott, Fiona
Abstract: This paper draws on an ESRC-funded study of play and creativity in preschool-aged children's use of apps in the UK. The main objectives of the study were to collect information about access to and use of apps in the home, establish the most popular apps and identify the features of those apps that are successful in promoting play and creativity. A mixed-method approach was used to collect data, including video filming of children using the most popular apps. In identifying play types that emerged in the analysis of data, the team utilised an established taxonomy, which outlines sixteen play types. This taxonomy was reviewed and adapted to analyse data from the project relating to digital play. Through this process, an additional type of play, transgressive play, was identified and added to the taxonomy. The paper outlines the implications of the revised taxonomy for future studies of play.